REFORMASI GEREJA INGGRIS 1529-1534: “AMBISI DAN KEWAJIBAN RAJA HENRY VIII” - Pipit Maysyaroh; Nana Supriatna (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This research entitled “Church Reform in England in 1529-1534: A Study of the Background of Establishment of Anglican Church in Britain”. The difference in characteristics of church reform in England is the background of this research. There are four main questions of research: (1) What was the situation of the Church of England before the Church Reform of 1534? (2) What were the factors of the Church’s Reformation in England in 1534? (3) How was the process of secession of the Church of England from the Roman Church in the Church Reformation of England in 1534? (4) How was the impact of the Church Reformation in England in 1534? The main purpose of this research is to describe about what happened during the Church Reformation process in Britain which took place in 1534. This study uses historical methods consisting of heuristics, criticism, interpretation and historiography. Based on research results, it was found that, one, the church situation in England is very bad. Corruption, demoralization, and veneration of relics become a culture. Two, Clement VII’s refusal to annul the marriage of King Henry VIII was the trigger of secession. Three, the process of separation is done through the Reform Parliament. The Act of Supremacy makes him the sole ruler of the Kingdom of England and Anglican Church. Four, the greatest impact was the religious crisis that occurred along the Tudor Dynasty, and the Kingdom of England became a country with complete sovereignty.